2019
DOI: 10.3174/ajnr.a5927
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Synthetic FLAIR Images with Deep Learning Using a Conditional Generative Adversarial Network for Pixel-by-Pixel Image Translation

Abstract: BACKGROUND AND PURPOSE: Synthetic FLAIR images are of lower quality than conventional FLAIR images. Here, we aimed to improve the synthetic FLAIR image quality using deep learning with pixel-by-pixel translation through conditional generative adversarial network training. MATERIALS AND METHODS:Forty patients with MS were prospectively included and scanned (3T) to acquire synthetic MR imaging and conventional FLAIR images. Synthetic FLAIR images were created with the SyMRI software. Acquired data were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…The results of the current study also revealed that the DL algorithm using CNN improved the image quality of the synthetic FLAIR images by correcting the typical artifacts in both quantitative and qualitative analyses, and it is consistent with the results of two recent studies [10,11]. In the current study, both NRMSE and PSNR values in the DL-FLAIR image were more distinctive in GM and CSF regions than in WM in the region-wise analyses, which is consistent with the quantitative analysis of the recent study [10].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the current study also revealed that the DL algorithm using CNN improved the image quality of the synthetic FLAIR images by correcting the typical artifacts in both quantitative and qualitative analyses, and it is consistent with the results of two recent studies [10,11]. In the current study, both NRMSE and PSNR values in the DL-FLAIR image were more distinctive in GM and CSF regions than in WM in the region-wise analyses, which is consistent with the quantitative analysis of the recent study [10].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, recent studies have developed DL algorithms using variants of CNN to remove synthetic FLAIR artifacts and have thus demonstrated the feasibility of this method. However, two studies presented limitations because they were conducted using the same 3T MR scanner provided by a single vendor, although the institutions were different [10,11]. Therefore, our results are promising for generalizing the application of the DL method for improving synthetic FLAIR image quality because overfitted DL models only work for internal datasets and exhibit poor performance for external datasets [20].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Further, up-and downsampling, scale aggregation, and preclassification with a multicolumn approach could also be used to increase the accuracy of crowd counting. On the other hand, deconvolution [65] and Generative Adversarial Networks (GANs) [66] can be employed to enhance the quality of a density map for medical applications.…”
Section: Motivation For Employing Cnn-based Image Crowd Countingmentioning
confidence: 99%